Estilos de crianza y tolerancia a la frustración en estudiantes. Unidad Educativa Comunitaria Intercultural Bilingüe Surupukyu. Guaranda, 2021 - Rea Chacha, Piedad Abigail (2021)
ABSTRACT The changes of the roles and family nucleus in the communities influence the socialization of Parenting Styles and can cause emotional alterations. This project sought to analyze parenting styles and frustration tolerance in students of "Unidad Educativa Comunitaria Intercultural Bilingüe Surupukyu" in Guaranda, 2021. It was a quantitative study of bibliographic and documentary type, descriptive and correlational level, and non- experimental, retrospective, and transversal design. The study sample was 90 students' folders between 12 and 17 years old. The data collection was through an observation sheet. It was registered the results of the Baumrind's Parenting Styles Questionnaire (1994) and Oliva's Frustration Tolerance Scale (2011). The Statistical Package for the Social Sciences (SPSS) version 25.0 was used to process the data. It was possible to identify that 32.2% of the students perceive permissive fathers and 31,1% as authoritarian mothers. Regard tolerance to frustration, 36,7% present high levels, 28.9% medium levels, and 34,4% low levels. To obtain correlation was used the chi-square test. It was rejected the relationship between paternal styles (sig. 0.953), maternal styles (sig. 0.617), the frustration tolerance. Therefore, no found a relationship between the study variables, and they may vary due to the cultural and ethnic diversity of the participants. Finally, with these results, was proposed an intervention protocol with a cognitive-behavioral approach to strengthening tolerance to frustration in the students. Keywords: Stiles, parenting, tolerance, frustration, students. Reviewed by: Mgs. Lorena Solís Viteri ENGLISH PROFESSOR c.c. 0603356783